Decomposable rubber composition, rubber member, sealing member, and method for producing degradable rubber composition
By adding a hydrolysis promoter and a hydrolysis inhibitor to the decomposition rubber composition, the hydrolysis rate of rubber molecules is adjusted, and the problem of difficult control of the hydrolysis and disintegration time of rubber components in fluids such as water in the prior art is solved, thereby realizing the sealing Effective control of functions and natural disintegration of rubber components.
Patent Information
- Application Number
- CN202380053769.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-18
AI Technical Summary
The time for the existing decomposition rubber members to dissolve and disintegrate in a fluid such as water is difficult to control, resulting in the loss of sealing function.
By adding a hydrolysis promoter and a hydrolysis inhibitor to the decomposition rubber composition, the hydrolysis rate of the rubber molecule is adjusted, thereby controlling the decomposition time of the rubber member in a fluid such as water.
The decomposition time of the rubber member is controlled in a fluid such as water, extends the maintenance time of the sealing function, and realizes the natural disintegration of the rubber member after a specified time.
Smart Images

Figure CN119487283A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a degradable rubber composition, a rubber member, a sealing member, and a method for producing the degradable rubber composition, and in particular to a degradable rubber composition, a rubber member, a sealing member, and a method for producing the degradable rubber composition, which can control the time from immersion in a fluid such as water to decomposition. Background Art
[0002] In the past, in order to extract hydrocarbon resources such as oil and natural gas in underground layers, the following methods were used: Figure 6 Hydraulic fracturing is shown. Figure 6 This is an explanatory diagram showing an overview of the hydraulic fracturing method. In the hydraulic fracturing method, first, an underground layer 50 is excavated from a pit 10 on the surface 11 by a drill bit or the like, and an excavation hole 13 is formed until a production layer 51 in which hydrocarbon resources are distributed and confined underground at a great depth of, for example, several thousand meters is reached. Next, a fluid such as water is injected into the formed excavation hole 13 at high pressure, thereby breaking the bedrock of the production layer 51 and causing cracks 15 in the bedrock of the production layer 51. The hydrocarbon resources confined in the production layer 51 are released from the cracks 15 thus generated (for example, refer to Patent Document 1).
[0003] In the hydraulic fracturing method, in order to generate cracks 15 in the production layer 51 by using the pressure of the fluid, it is necessary to seal the excavation hole 13 at one or more locations using a sealing member 100 such as a fracturing plug, so that a space sealed by the sealing member 100 is formed in a part of the excavation hole 13. At this time, the sealing member 100 needs to prevent the fluid from flowing out of the space.
[0004] On the other hand, in order to extract the hydrocarbon resources released by the hydraulic fracturing method through the excavation hole 13, it is necessary to remove the sealing member 100 from the excavation hole 13. As a method for making it easy to remove the sealing member 100 from the excavation hole 13, there is a method of using the sealing member 100 in the excavation hole 13, wherein the sealing member 100 is decomposed by being exposed to an environment with a fluid such as water for a predetermined time. As such a sealing member 100, for example, a sealing member composed of a resin member and a rubber member is known, wherein the resin member is formed of a decomposable resin such as polylactic acid, and the rubber member is formed of a decomposable rubber component.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-59376 Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] However, it is known that the time until the rubber member formed of the above-mentioned degradable rubber component is hydrolyzed and disintegrated in the presence of a fluid such as water can be controlled by adjusting the amount of a decomposition accelerator, etc., but the degree of decomposition generally occurs linearly with the passage of time. If the time from contact with a fluid such as water to actual use is long, the function as a sealing member may be lost. Therefore, a rubber member is required that can control the time from immersion in a fluid such as water to the start of decomposition.
[0010] The present invention has been made in view of the above circumstances, and an exemplary technical problem thereof is to provide a degradable rubber composition, a rubber member, a sealing member, and a method for producing the degradable rubber composition, which can control the time from immersion in a fluid such as water to the start of decomposition.
[0011] Technical solutions for solving technical problems
[0012] In order to solve the above-mentioned technical problems, the present invention has the following configurations.
[0013] (1) A degradable rubber composition comprising: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator which promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an acidic hydrolysis accelerator in the form of a powder which exhibits acidity by contact with water, wherein the acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more per 100 parts by mass of the degradable rubber component.
[0014] (2) A degradable rubber composition comprising: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator which promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an alkaline hydrolysis accelerator in the form of a powder which exhibits alkalinity by contact with water, wherein the alkaline hydrolysis accelerator is contained in an amount of 1 part by mass or more per 100 parts by mass of the degradable rubber component.
[0015] (3) A rubber member formed from the degradable rubber composition described in (1) above.
[0016] (4) A sealing member including the rubber member described in (3) above as at least a part thereof.
[0017] (5) A method for producing a degradable rubber composition, comprising a kneading step of kneading raw materials, wherein the raw materials contain: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator which promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an acidic hydrolysis accelerator in the form of a powder which exhibits acidity by contact with water, wherein the acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more per 100 parts by mass of the degradable rubber component.
[0018] (6) A method for producing a degradable rubber composition, comprising a kneading step of kneading raw materials, wherein the raw materials contain: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator which promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an alkaline hydrolysis accelerator in the form of a powder which exhibits alkalinity by contact with water, wherein the alkaline hydrolysis accelerator is contained in an amount of 1 part by mass or more per 100 parts by mass of the degradable rubber component.
[0019] Hereinafter, further objects and other features of the present invention will be described through preferred embodiments described with reference to the accompanying drawings.
[0020] Effects of the Invention
[0021] According to the present invention, it is possible to provide a degradable rubber composition, a rubber member, a sealing member, and a method for producing a degradable rubber composition, which can control the time from immersion in a fluid such as water to the start of decomposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram showing a sealing member formed using the degradable rubber composition of the first embodiment.
[0023] Figure 2 This is a graph showing the results of measuring the surface hardness of the rubber samples of Examples 1 and 2 and Comparative Examples 1 to 3.
[0024] Figure 3 Schematic diagram showing the state of the rubber sample of Example 1 before and after natural disintegration.
[0025] Figure 4 This is a graph showing the temperature dependency of the degradable rubber composition of Example 3.
[0026] Figure 5 This is a graph showing the dependency of the degradable rubber composition of Example 4 on a hydrolysis accelerator.
[0027] Figure 6 This is an explanatory diagram showing an outline of a conventional hydraulic fracturing method. DETAILED DESCRIPTION
[0028] [Implementation Method 1]
[0029] Hereinafter, the degradable rubber composition according to the first embodiment (hereinafter, sometimes simply referred to as “degradable rubber composition”) will be described.
[0030] [Degradable rubber composition]
[0031] The decomposable rubber composition contains a decomposable rubber component, a hydrolysis accelerator and a hydrolysis inhibitor, and is suitable for use as a material of a rubber component constituting a sealing component used in a hydraulic fracturing method. The rubber component formed using the decomposable rubber composition has the sealing performance of a rubber component as a sealing component during the first period even if it is exposed to a fluid such as water. In the present embodiment, the "first period" refers to the period during which the rubber component formed using the decomposable rubber composition maintains the sealing performance of a rubber component as a sealing component even if it is exposed to a fluid such as water. The first period may be, for example, several days, 5 days, 7 days, etc., and may be appropriately adjusted based on the combination composition of the hydrolysis accelerator, hydrolysis inhibitor, etc. described later.
[0032] In addition, the rubber component formed using the degradable rubber composition has the following characteristics, that is, it disintegrates after further continuous exposure to a fluid such as water during a second period. Here, the "second period" refers to the time until the rubber component disintegrates after the first period when the rubber component is further continuously exposed to a fluid such as water. The second period is, for example, several days, 4 days, 6 days, etc., which can be appropriately adjusted based on the composition of the hydrolysis accelerator, hydrolysis inhibitor, etc. described later.
[0033] Here, the "disintegration" of the rubber component means that after the rubber component is continuously exposed to a fluid such as water for a specified period of time, the rubber molecules constituting the rubber component are hydrolyzed and the shape of the rubber component is disintegrated. If the temperature conditions are different, the "first period" and the "second period" may also change, and the performance of the rubber component needs to be evaluated under certain conditions. In this embodiment, the time (first period or second period) until the rubber component disintegrates is evaluated under certain conditions of continuous exposure in water at 93°C. In the past, it was known that when continuously exposed in water at 93°C, it takes a specified number of days (e.g., 7 days) for the surface hardness (HsA) of a rubber component composed of hydrolyzable rubber molecules to become 0 (zero).
[0034] Here, the "disintegration" of the rubber component also includes the "natural disintegration" of the rubber component. The "natural disintegration" of the rubber component means that after the rubber component is continuously exposed to a fluid such as water for a specified period of time, the rubber component cannot maintain its shape and disintegrates into small pieces. For example, at the stage where the hardness of the degradable rubber component is 0, the situation where small pieces are formed even without external force is also included in the natural disintegration. It should be noted that the surface hardness (HsA) of the rubber component becomes 0 (zero) and is different from the natural disintegration of the rubber component. That is, even if the surface hardness (HsA) of the rubber component is 0 (zero), there is a situation where the shape of the rubber component is maintained, and if no stress is applied from the outside of the rubber component, it will not be fragmented. Below, each component of the degradable rubber composition is explained in turn. It should be noted that the details of the hydraulic fracturing method and the sealing component are described below.
[0035] [Degradable rubber component]
[0036] The degradable rubber component contains rubber molecules that can be hydrolyzed. As the rubber molecules that can be hydrolyzed, it is preferred that the rubber molecules have a functional group that can be hydrolyzed in the main chain of the rubber molecules. The rubber molecules may have a functional group that can be hydrolyzed not only in the main chain but also in the cross-linked part. Examples of the functional group that can be hydrolyzed include a carbamate group, an ester group, an amide group, a carboxyl group, a hydroxyl group, a silyl group, and the like. A part of the repeating units constituting the rubber molecule may have a functional group that can be hydrolyzed, or all of them may have a functional group that can be hydrolyzed. As materials containing rubber molecules that can be hydrolyzed, there are, for example, mixing-type rubber materials, and the like.
[0037] Here, "kneading type rubber material" refers to a kneading type rubber material, i.e., a rubber material that can be kneaded. The kneading type rubber material is a rubber material that is solid at room temperature in the state before vulcanization, and is distinguished from the liquid injection type rubber material. The kneading type rubber material is solid at room temperature, and therefore, for example, is suitable for kneading using a kneader, a roller, etc., and even if a large amount of powdered additives are added, the additives can be uniformly dispersed in the kneading type rubber material by kneading. It should be noted that in the case of the liquid injection type rubber material, since it is a liquid at room temperature, if a large amount of powdered additives are added, sometimes the solubility limit is reached, phase separation occurs, or the additives clump and are difficult to disperse uniformly.
[0038] As the kneading type rubber material, there can be cited materials containing at least one selected from polyurethane rubber, natural rubber, isoprene rubber, ethylene propylene rubber, butyl rubber, styrene rubber, acrylic rubber, aliphatic polyester rubber, and chloroprene rubber. It should be noted that in the present embodiment, thermoplastic elastomers such as polyester thermoplastic elastomers and polyamide thermoplastic elastomers, which are materials having properties similar to those of the kneading type rubber material, can also be included in the concept of the kneading type rubber material.
[0039] The mass average molecular weight of the rubber molecules constituting the kneading type rubber material is preferably, for example, 10,000 or more. If the mass average molecular weight is 10,000 or more, there is a tendency that the handling operability as the kneading type rubber becomes good. It should be noted that by adjusting the mass average molecular weight of the rubber molecules constituting the kneading type rubber material according to the content ratio of the hydrolysis accelerator and the hydrolysis inhibitor described later, it is possible to control the time from exposure to a fluid such as water to the natural disintegration of the rubber member.
[0040] As a millable rubber material, polyurethane rubber is preferred from the viewpoint of controlling the sealing performance such as hardness and elasticity as a rubber component and controlling the decomposition performance and disintegration performance. Polyurethane rubber includes ester type polyurethane rubber, ether type polyurethane rubber, etc., and ester type polyurethane rubber with a hydrolyzable functional group is particularly preferred. In addition, polyurethane rubber, in addition to the millable type, also includes thermoplastic type, liquid injection type, etc., but since the hydrolysis accelerator described later is a powder, in order to make the decomposable rubber composition contain a hydrolysis accelerator of more than a specified amount, a millable type polyurethane rubber is preferred.
[0041] The degradable rubber component preferably contains a kneaded rubber material as a main component. The degradable rubber component may contain a rubber material other than the kneaded rubber material as long as the properties of the kneaded rubber material used in the present embodiment are not affected.
[0042] [Hydrolysis accelerator]
[0043] The hydrolysis accelerator is a powder that shows acidity or alkalinity by contact with water, and is a component that promotes the hydrolysis of rubber molecules of the degradable rubber component. Here, "powder" refers to a substance that is in powder or granular form at room temperature and in a state not in contact with water (dry state), and the particle size is less than 200μm. When the powder is in contact with water, its aqueous solution is acidic or alkaline. The hydrolysis of rubber molecules is promoted by the acidic or alkaline aqueous solution. In the present embodiment, the powder that shows acidity by contact with water and promotes the hydrolysis of rubber molecules of the degradable rubber component by contact with water is referred to as an acidic hydrolysis accelerator. In the present embodiment, the powder that shows alkalinity by contact with water and promotes the hydrolysis of rubber molecules of the degradable rubber component by contact with water is referred to as an alkaline hydrolysis accelerator.
[0044] As the acidic hydrolysis accelerator, for example, mineral powders such as silicon dioxide, clay, talc, aluminum sulfate, barium sulfate, calcium sulfate, and alumina colloid can be cited. It should be noted that the acidic hydrolysis accelerator is not limited to mineral powders. As the acidic hydrolysis accelerator, these substances can be used alone, or a plurality of substances can be used in combination.
[0045] In the decomposable rubber composition, the content ratio of the acidic hydrolysis accelerator is 10 parts by mass or more relative to 100 parts by mass of the decomposable rubber component, preferably 20 parts by mass or more, more preferably 40 parts by mass or more, and particularly preferably 40 parts by mass. If the content ratio of the acidic hydrolysis accelerator is 10 parts by mass or more, the decomposable rubber component is decomposed, and the decomposed substance (hereinafter referred to as the decomposed product) becomes clay-like and maintains the clay-like shape. If the content ratio of the acidic hydrolysis accelerator is 20 parts by mass or more, the decomposed product disintegrates due to external force. If the content ratio of the acidic hydrolysis accelerator is 40 parts by mass or more, the decomposed product disintegrates naturally without applying external force. By making the content ratio of the acidic hydrolysis accelerator in the decomposable rubber composition 40 parts by mass or more relative to 100 parts by mass of the decomposable rubber component, a decomposable rubber composition constituting a sealing member can be obtained, wherein the sealing member is exposed to a fluid such as water for a specified time to appropriately disintegrate the rubber molecules naturally, and can be easily removed by flakes even if stress is not applied from the outside.
[0046] As the alkaline hydrolysis accelerator, for example, alkaline oxides such as metal oxide particles, salts of weak acids and strong bases, or metal hydroxides can be mentioned. As the alkaline oxide, for example, magnesium oxide, potassium oxide, or calcium oxide can be mentioned. As the salt of weak acids and strong bases, for example, sodium carbonate, sodium bicarbonate, or calcium carbonate can be mentioned. As the metal hydroxide, for example, sodium hydroxide or potassium hydroxide can be mentioned. It should be noted that the alkaline hydrolysis accelerator is not limited to the above-mentioned alkaline oxides, salts of weak acids and strong bases, or metal hydroxides. As the alkaline hydrolysis accelerator, these substances can be used alone, or a variety of substances can be used in combination.
[0047] In the degradable rubber composition, the content of the alkaline hydrolysis accelerator is 1 part by mass or more relative to 100 parts by mass of the degradable rubber component. By setting the content of the alkaline hydrolysis accelerator in the degradable rubber composition to 1 part by mass or more relative to 100 parts by mass of the degradable rubber component, the hydrolysis of the rubber molecules can be further accelerated by continuous exposure to a fluid such as water, thereby shortening the time until the rubber molecules naturally disintegrate.
[0048] The hydrolysis accelerator may include an acidic hydrolysis accelerator, an alkaline hydrolysis accelerator, or both. As described above, by containing 40 parts by mass or more of the acidic hydrolysis accelerator relative to 100 parts by mass of the decomposable rubber composition, the natural disintegration of the rubber member is produced, and the alkaline hydrolysis accelerator has the effect of accelerating the decomposition of the rubber member. By appropriately adjusting these effects, the natural disintegration and decomposition speed of the rubber member can be adjusted.
[0049] [Hydrolysis Inhibitor]
[0050] The hydrolysis inhibitor is a component that inhibits the hydrolysis of rubber molecules promoted by the hydrolysis accelerator. As the hydrolysis inhibitor, for example, a component that reacts with carboxylic acid at the carboxyl terminal generated by the hydrolysis of the rubber molecules and inhibits the chain reaction of the hydrolysis reaction can be used.
[0051] Examples of the hydrolysis inhibitor include polymer carbodiimide compounds, etc. As the hydrolysis inhibitor, these may be used alone or in combination of a plurality of them.
[0052] The properties of the hydrolysis inhibitor are not particularly limited, and for example, a powdered hydrolysis inhibitor may be used. By using a kneading type rubber material, the powdered hydrolysis inhibitor can be kneaded well.
[0053] In the decomposable rubber composition, the content of the hydrolysis inhibitor is preferably 1 part by mass or more relative to 100 parts by mass of the decomposable rubber component. The content of the hydrolysis inhibitor in the decomposable rubber composition is appropriately adjusted according to the mass average molecular weight of the mixing rubber material and the content of the hydrolysis accelerator, so that the hydrolysis of the rubber molecules can be delayed and the sealing function as a sealing member can be maintained. That is, by increasing the content of the hydrolysis inhibitor in the decomposable rubber composition, the decomposition of the decomposable rubber composition can be further delayed.
[0054] [Other ingredients]
[0055] The degradable rubber composition may contain, in addition to the above-mentioned components, for example, a reinforcing agent as appropriate.
[0056] The reinforcing agent is added to improve the strength of the rubber member when the decomposable rubber composition is used as a sealing member. As the reinforcing agent, for example, silicon dioxide, carbon black, etc. can be cited. It should be noted that when a mineral powder such as silicon dioxide is used as an acidic hydrolysis accelerator, the mineral powder can play two functions as an acidic hydrolysis accelerator and as a reinforcing agent. As the acidic hydrolysis accelerator, for example, mineral powders such as silicon dioxide, clay, talc, aluminum sulfate, barium sulfate, calcium sulfate, and aluminum oxide colloid can be cited.
[0057] [Method for producing degradable rubber composition]
[0058] The method for producing the degradable rubber composition is not particularly limited, and a common production method can be used. That is, the degradable rubber composition can be produced, for example, by a production method including the following steps: a kneading step in which raw materials containing at least a degradable rubber component and an acidic hydrolysis accelerator are kneaded; and a vulcanization step in which the kneaded raw materials are subjected to a crosslinking reaction.
[0059] The kneading method for kneading the raw materials in the kneading step is not particularly limited, and the kneading may be carried out by an open roll mill, a pressure kneader, a Banbury mixer or the like.
[0060] After the degradable rubber composition is obtained, there is no particular limitation on the method for producing a rubber member. For example, the degradable rubber member can be produced by placing the degradable rubber composition in a predetermined mold and vulcanizing it under predetermined vulcanization conditions.
[0061] Regarding the vulcanization conditions for vulcanizing the degradable rubber composition, for example, the temperature can be set to a range of 120°C to 200°C and a time of about 5 to 60 minutes. When the temperature is lower than 120°C, the crosslinking agent is not decomposed and the crosslinking reaction of the rubber does not occur. In addition, if the temperature exceeds 200°C, the compound (polymer) is degraded. On the other hand, in the range of 120°C to 200°C, crosslinking of the rubber occurs and degradation of the polymer does not occur. The range of time is the same. As a vulcanizing agent, sulfur or an organic peroxide can be used. As an organic peroxide, for example, peroxy ketal, dialkyl peroxide, diacyl peroxide, peroxy ester, etc. can be cited.
[0062] [Hydraulic fracturing]
[0063] Next, hydraulic fracturing is described. As an example of using the sealing member of this embodiment, hydraulic fracturing is described. Figure 6 The method is the same as described in Figure 6 However, as described later, the sealing member of the present embodiment is formed using the degradable rubber composition according to the present embodiment, and the material of the rubber member is different from that of the conventional sealing member 100 .
[0064] [Sealing member 1]
[0065] Figure 1 Schematic diagram showing a sealing member formed using the degradable rubber composition according to Embodiment 1. Figure 1 As shown, the sealing component 1 includes: a main body 2 having a roughly cylindrical shape extending along the length direction L; a pair of sleeves 4, which are arranged on both end sides of the length direction L of the main body 2 in a manner that allows sliding along the length direction L; and a rubber component 3, which is arranged between the pair of sleeves 4. Figure 1 (a) is a schematic diagram showing a state in which the pair of sleeves 4 are located at predetermined positions and the rubber member 3 is not compressed. Figure 1(b) is a schematic diagram showing a state in which the pair of sleeves 4 are located at a position moved toward the center side (rubber member 3 side) in the length direction L, and the rubber member 3 is compressed. Here, the "length direction L" is the direction in which the substantially cylindrical tube of the sealing member 1 extends, and refers to the direction in which the central axis extends, and is the direction in which the sealing member 1 moves in the excavated hole 13. In addition, the "two end sides in the length direction L" refer to the front end side and the rear end side when the sealing member 1 moves in the excavated hole 13.
[0066] [Rubber member 3]
[0067] The rubber member 3 is a member formed of the degradable rubber composition according to the first embodiment. As described above, the rubber member 3 is disposed between the pair of sleeves 4 and is a tubular member covering the periphery of the main body 2. Figure 1 As shown in (b), the rubber member 3 is deformed by being compressed by the pair of sleeves 4 and expands in a direction substantially perpendicular to the longitudinal direction. As a result, the diameter (diameter substantially perpendicular to the longitudinal direction) of the sealing member 1 increases in the portion of the rubber member 3. In this way, the rubber member 3 is tightly attached to the wall surface of the excavated hole 13 by the expansion of the rubber member 3, and the excavated hole 13 can be sealed.
[0068] After the sealing member 1 has finished sealing the excavation hole 13, the rubber member collapses naturally and is removed. The rubber member 3 is formed by the decomposable rubber composition involved in this embodiment. The decomposable rubber composition of the rubber member 3 constituting the sealing member 1 has a sealing function and has a function of flakes even if no stress is applied from the outside after a predetermined time. The parts other than the rubber member 3 constituting the sealing member 1, namely the main body 2 and a pair of sleeves 4, can be formed by the decomposable rubber composition or by other decomposable raw materials. As such decomposable raw materials, for example, polyglycolic acid (PGA), polylactic acid (PLA) and the like can be cited. The parts other than the rubber member 3 constituting the sealing member 1 are preferably decomposed in a time substantially equal to the decomposition time of the decomposable rubber composition. It should be noted that the decomposable rubber composition of this embodiment is not limited to the above-mentioned hydraulic fracturing method, and can also be used in other methods requiring sealing performance, decomposition performance and disintegration performance.
[0069] [Example]
[0070] Hereinafter, specific examples of the present invention will be described by way of examples. It should be noted that the present invention is not limited to the following examples.
[0071] [Example 1]
[0072] As raw materials, 100 parts by mass of polyester-based kneadable polyurethane rubber as a degradable rubber component, 40 parts by mass of silica as an acidic hydrolysis accelerator and reinforcing agent, and 3 parts by mass of a high molecular weight carbodiimide compound as a hydrolysis inhibitor were used. The degradable rubber component was kneaded using an open roll mill, and the hydrolysis accelerator and hydrolysis inhibitor were added as additives, and further kneaded to obtain the degradable rubber composition of Example 1.
[0073] The obtained decomposable rubber composition was put into a mold and heated under pressure at 120-200° C. for 60 minutes to vulcanize. An organic peroxide was used as a vulcanizing agent. A cubic rubber sample with one side of 20 mm was prepared. A plurality of rubber samples were prepared corresponding to each immersion time described later.
[0074] [Decomposability evaluation test]
[0075] Each rubber sample and ion exchange water having a volume 10 times the volume of the rubber sample were added to a 200 mL glass bottle, and each rubber sample and ion exchange water were placed in an oven set at 93° C. for a predetermined immersion time. The immersion time was 1 day, 3 days, 5 days, 7 days, 9 days, and 11 days.
[0076] Each rubber sample after being placed in the oven for each immersion time was taken out from the ion exchange water and placed at room temperature to dry. Then, for each rubber sample, the surface hardness (HsA) was measured using a hardness meter type A (JIS K 6253, Kobunsu Keiki Co., Ltd.). The surface hardness was measured as the value after applying a load of 1 kg for 3 seconds. It should be noted that as the surface hardness on day 0, the value measured before the rubber sample was immersed in the ion exchange water was used.
[0077] The results of surface hardness measurement are shown in Figure 2 . Figure 2 : is a graph showing the results of measuring the surface hardness of the rubber samples of Examples 1 and 2 and Comparative Examples 1 to 3. Figure 2 In the graph of , the vertical axis represents the surface hardness (HsA) and the horizontal axis represents the immersion time (days). Figure 2 Indicated by "▲" (black ▲) in the figure. The surface hardness of the rubber sample of Example 1 was maintained about 5 days after the start of immersion, and then decreased. Based on the comparison with Comparative Example 1 described later, it is estimated that the hydrolysis of the rubber member was suppressed until about 5 days after the start of immersion due to the effect of the hydrolysis inhibitor. It can be seen that the surface hardness (HsA) of the rubber sample of Example 1 became 0 (zero) 9 days after the start of immersion.
[0078] The rubber sample of Example 1 was immersed for 9 days, as described below. Figure 3 (b) shows natural disintegration. Figure 2As can be seen from the graph, the surface hardness of the rubber sample of Example 1 was maintained at about 80 HsA from the start of immersion to about the fifth day, and then the surface hardness decreased to 0 HsA. It is inferred that the rubber sample of Example 1 was able to suppress the decrease in surface hardness from the start of immersion to about the fifth day due to the action of the hydrolysis inhibitor, and then the surface hardness decreased by the hydrolysis of the degradable rubber component. In the rubber sample of Example 1, the first period was the period from the start of immersion to about the fifth day, and the second period was the period from about the fifth day to about the ninth day. Figure 2 In FIG. 1 , the first period and the second period of the rubber sample of Example 1 are indicated by double arrows.
[0079] Figure 3 Schematic diagram showing the state of the rubber sample of Example 1 before and after natural disintegration. Figure 3 (a) is a schematic diagram showing the state immediately after the rubber sample 30 is prepared. At this point, the rubber sample 30 maintains a cubic shape with one side of 20 mm, and the decomposable rubber component has not been decomposed. It should be noted that the state before immersion is not limited to Example 1, and is the same in other Examples and Comparative Examples. Figure 3 (b) shows that a glass bottle 34 containing ion exchange water 36 is placed. Figure 3 (a) is a schematic diagram of the state of the rubber sample 30 after natural disintegration 9 days after the start of immersion. Figure 3 (b) shows a state where small pieces 32 of the naturally disintegrated rubber sample 30 are precipitated in ion-exchanged water 36 at the bottom of a glass bottle 34 . Figure 3 The small pieces 32 of the naturally disintegrated rubber sample 30 shown in (b) are, for example, fragmented to less than 1 mm and are in a powdery state when taken out of the glass bottle 34. This shows that the rubber sample 30 of Example 1 disintegrated naturally 9 days after the start of immersion.
[0080] [Example 2]
[0081] The rubber samples were prepared and the surface hardness (HsA) was measured in the same manner as in Example 1, except that 4.5 parts by mass of a high molecular weight carbodiimide compound was added as a hydrolysis inhibitor to 100 parts by mass of the degradable rubber component. Figure 2Indicated by "■" (black rectangle). The rubber sample of Example 2 maintained its surface hardness 5 days after the start of immersion and then decreased. Based on the comparison with Comparative Example 1 described later, it is inferred that the hydrolysis of the rubber component was suppressed until about 5 days after the start of immersion due to the effect of the hydrolysis inhibitor. It can be seen that the surface hardness (HsA) of the rubber sample of Example 2 became 0 (zero) 11 days after the start of immersion. The rubber sample of Example 2 disintegrated naturally 11 days after the start of immersion, similar to Example 1. It can be seen that the hydrolysis of the degradable rubber component was suppressed by adding the hydrolysis inhibitor.
[0082] Depend on Figure 2 As can be seen from the graph, the surface hardness of the rubber sample of Example 2 is maintained at about 80HsA from the start of dipping to about the 5th day, and then the surface hardness decreases to 0HsA. It is speculated that the rubber sample of Example 2 can suppress the decrease in surface hardness from the start of dipping to about the 5th day by the action of the hydrolysis inhibitor, and then the surface hardness is reduced by hydrolyzing the degradable rubber component. In addition, it is speculated that the amount of hydrolysis inhibitor added to the rubber sample of Example 2 is large compared with Example 1, so even after the 5th day from the start of dipping, the hydrolysis can be suppressed by the action of the hydrolysis inhibitor, the decrease in surface hardness (the slope of the graph) becomes slower, and the time from the start of dipping to disintegration becomes longer. In the rubber sample of Example 2, the first period is the period from the start of dipping to about the 5th day, and the second period is the period from about the 5th day to about the 11th day.
[0083] [Comparative Example 1]
[0084] The rubber samples were prepared in the same manner as in Example 1 except that the hydrolysis inhibitor was not added, and the surface hardness (HsA) was measured. Figure 2 It is indicated by "○" (open circle) in the figure. It is known that the surface hardness (HsA) of the rubber sample of Comparative Example 1 becomes 0 (zero) 7 days after the start of immersion. It is presumed that the rubber sample of Comparative Example 1 hydrolyzes immediately after immersion because it does not contain a hydrolysis inhibitor.
[0085] [Comparative Example 2]
[0086] The rubber samples were prepared and the surface hardness (HsA) was measured in the same manner as in Comparative Example 1, except that 5 parts by mass of magnesium oxide, a basic hydrolysis accelerator, was used as a hydrolysis accelerator instead of the acidic hydrolysis accelerator (silicon dioxide) relative to 100 parts by mass of the degradable rubber component. Figure 2In the figure, "△" (hollow triangle) is used to indicate the surface hardness (HsA) of the rubber sample of Comparative Example 2, which becomes 0 (zero) one day after the start of immersion. It is speculated that the rubber sample of Comparative Example 2 does not contain a hydrolysis inhibitor, so it is hydrolyzed immediately after immersion. In addition, it is speculated that the rubber sample of Comparative Example 2 contains an alkaline hydrolysis accelerator, which promotes hydrolysis and reduces the surface hardness quickly.
[0087] [Comparative Example 3]
[0088] The rubber samples were prepared and the surface hardness (HsA) was measured in the same manner as in Comparative Example 1, except that 3 parts by mass of magnesium oxide, a basic hydrolysis accelerator, was used as a hydrolysis accelerator instead of the acidic hydrolysis accelerator (silicon dioxide) relative to 100 parts by mass of the degradable rubber component. Figure 2 Indicated by "□" (hollow quadrilateral). It can be seen that the surface hardness (HsA) of the rubber sample of Comparative Example 3 becomes 0 (zero) 3 days after the start of immersion. It is speculated that the rubber sample of Comparative Example 3 is hydrolyzed immediately after immersion because it does not contain a hydrolysis inhibitor. In addition, it is speculated that the rubber sample of Comparative Example 3 contains an alkaline hydrolysis accelerator, which promotes hydrolysis and reduces the surface hardness quickly. Compared with the rubber sample of Comparative Example 2, the rubber sample of Comparative Example 3 contains a smaller content of the alkaline hydrolysis accelerator, so it is speculated that the promotion effect of hydrolysis is smaller than that of Comparative Example 2, and the reduction of the surface hardness is not as fast as that of Comparative Example 2.
[0089] As described above, the degradable rubber composition according to the present invention can suppress hydrolysis by containing a hydrolysis inhibitor, and can form a rubber member in which the period (first period and second period) until disintegration is adjustable.
[0090] [Example 3: Regarding temperature dependence]
[0091] The temperature dependence of the degradable rubber composition is described. As the rubber sample, 100 parts by mass of polyester-based kneaded polyurethane rubber as a degradable rubber component and 40 parts by mass of silica as an acidic hydrolysis accelerator and reinforcing agent are used as raw materials. It should be noted that no hydrolysis inhibitor is added. In addition, no hydrolysis accelerator such as a metal oxide is added. The temperature of the ion exchange water (hereinafter referred to as the water temperature) in which the rubber sample is immersed is set to 73°C, 93°C, and 113°C.
[0092] Figure 4 This is a graph showing how the surface hardness (HsA) that changes over time using the above rubber samples depends on the water temperature of the ion-exchanged water. Figure 4 The horizontal axis represents the immersion time (days), and the vertical axis represents the surface hardness (HsA). Figure 4In the graph of , when the surface hardness is 0, the degradable rubber composition disintegrates. Figure 4 In the figure, the graph indicated by "○" indicates the case where the water temperature is 73°C, the graph indicated by "●" indicates the case where the water temperature is 93°C, and the graph indicated by "×" indicates the case where the water temperature is 113°C.
[0093] The rubber sample immersed in ion exchange water at a water temperature of 73°C maintained a surface hardness (HsA) of 60 or more even on the 11th day from the start of immersion. The rubber sample immersed in ion exchange water at a water temperature of 93°C maintained a surface hardness (HsA) of 60 or more from the start of immersion to the third day, but the surface hardness decreased after 3 days, and the surface hardness (HsA) was 0 on the 7th day. The rubber sample immersed in ion exchange water at a water temperature of 113°C maintained a surface hardness (HsA) of 60 or more from the start of immersion to the first day, but the surface hardness decreased after 1 day, and the surface hardness (HsA) was less than 10 on the second day, and the surface hardness (HsA) was 0 on the third day.
[0094] As described above, it is known that the time until the degradable rubber composition disintegrates depends on the temperature of the liquid (ion-exchanged water) in which the rubber sample is immersed. Specifically, it is known that the higher the temperature of the ion-exchanged water, the shorter the time until the rubber sample disintegrates.
[0095] [Example 4: Dependence on the amount of hydrolysis accelerator added]
[0096] The dependence of the amount of hydrolysis accelerator added to the degradable rubber composition is described. Five rubber samples, S1, S2, S3, S4, and S5, are used. Here, the rubber sample S1 is the same as the above-mentioned Example 3, and the description is omitted. The rubber sample S2 is formulated with 40 parts by mass of silica as an acidic hydrolysis accelerator and reinforcing agent and 1 part by mass of a metal oxide as a hydrolysis accelerator relative to 100 parts by mass of the polyester-based kneaded polyurethane rubber. The rubber sample S3 is formulated with 40 parts by mass of silica as an acidic hydrolysis accelerator and reinforcing agent and 5 parts by mass of a metal oxide as a hydrolysis accelerator relative to 100 parts by mass of the polyester-based kneaded polyurethane rubber. The rubber sample S4 is formulated with 40 parts by mass of silica as an acidic hydrolysis accelerator and reinforcing agent and 10 parts by mass of a metal oxide as a hydrolysis accelerator relative to 100 parts by mass of the polyester-based kneaded polyurethane rubber. Rubber sample S5 is prepared by mixing 40 parts by mass of silica as an acidic hydrolysis accelerator and reinforcing agent and 20 parts by mass of metal oxide as a hydrolysis accelerator with respect to 100 parts by mass of polyester-based millable polyurethane rubber. It should be noted that in rubber samples S2 to S5, no hydrolysis inhibitor was added in order to clarify the addition amount dependency of the hydrolysis accelerator.
[0097] Figure 5This is a graph showing how the surface hardness that changes over time using the above rubber samples depends on the amount of hydrolysis accelerator added. Figure 5 The horizontal axis represents the immersion time (days), and the vertical axis represents the surface hardness (HsA). Figure 5 In the graph of , when the surface hardness is 0, the degradable rubber composition disintegrates. Figure 5 In the figure, the solid line represents the rubber sample S1, the dotted line represents the rubber sample S2, the dashed line with a small spacing represents the rubber sample S3, the dashed line with a large spacing represents the rubber sample S4, and the dashed-dotted line represents the rubber sample S5. It should be noted that the water temperature of the ion exchange water is 93°C.
[0098] The water temperature of rubber sample S1 is the same as that of Example 3, 93°C, and the description thereof is omitted. The surface hardness (HsA) of rubber sample S2 was maintained at 60 or more from the start of immersion to the third day, but the surface hardness decreased thereafter, and the surface hardness was (HsA) 0 on the ninth day. The surface hardness (HsA) of rubber sample S3 was maintained at 60 or more from the start of immersion to the second day, but the surface hardness (HsA) was 40 or less on the third day, (HsA) 10 on the fifth day, and (HsA) 0 on the seventh day. The surface hardness of rubber sample S4 began to decrease immediately after the start of immersion, and the surface hardness was (HsA) 30 on the first day, and (HsA) 0 on the second day. The surface hardness of rubber sample S5 began to decrease immediately after the start of immersion, and the surface hardness was (HsA) 0 on the first day.
[0099] As can be seen from the above, regarding rubber samples S2, S3, S4, and S5, the more the amount of the hydrolysis accelerator of the degradable rubber composition, specifically the metal oxide, is blended, the shorter the time required for the degradable rubber composition to decompose. However, it is known that when silica (acidic) and the metal oxide are used together, due to the neutralization effect, in the case of a small amount of the metal oxide blended (for example, 1 part by mass) such as rubber sample S2, the time required for decomposition becomes longer (9 days) compared to the time required for decomposition (7 days) of rubber sample S1 in which no metal oxide is blended.
[0100] As described above, the degradable rubber composition of the present embodiment contains 40 parts by mass of an acidic hydrolysis accelerator and a reinforcing agent (e.g., silica) relative to 100 parts by mass of a degradable rubber component (e.g., polyester-based kneadable polyurethane rubber). In addition, the degradable rubber composition can control the first period and the second period by adding a hydrolysis accelerator (e.g., a metal oxide) and a hydrolysis inhibitor (e.g., a polymer carbodiimide compound) as additives and adjusting their blending amounts, and can control the time until disintegration as a whole.
[0101] Although preferred embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications and changes can be made within the scope of the gist of the present invention. For example, the present invention includes the following gist.
[0102] (Subject 1) The present invention comprises: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator which promotes the hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits the hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an acidic hydrolysis accelerator in the form of a powder which exhibits acidity by contact with water, wherein the amount of the acidic hydrolysis accelerator contained is 40 parts by mass or more relative to 100 parts by mass of the degradable rubber component.
[0103] According to the first aspect, a degradable rubber composition can be provided, which can control the time from immersion in a fluid such as water to the start of decomposition. In addition, hydrolysis can be accelerated until the rubber member disintegrates naturally.
[0104] (Subject 2) The present invention comprises: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator which promotes the hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits the hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an alkaline hydrolysis accelerator in the form of a powder which exhibits alkalinity by contact with water, and the amount of the alkaline hydrolysis accelerator contained is 1 part by mass or more relative to 100 parts by mass of the degradable rubber component.
[0105] According to the second aspect, the hydrolysis of the rubber member can be accelerated and the time until the rubber member disintegrates can be shortened.
[0106] (Subject 3) The degradable rubber component may include a kneading type rubber material.
[0107] According to the third aspect, even if the content ratio of the powdery acidic hydrolysis accelerator is 40 parts by mass or more relative to 100 parts by mass of the degradable rubber component, the powdery acidic hydrolysis accelerator can be well dispersed in the degradable rubber composition.
[0108] (Subject 4) The mass average molecular weight of the rubber molecules may be 10,000 or more.
[0109] According to the fourth aspect, it is possible to select a kneading type rubber material within a range more suitable for controlling the magnitude of hydrolysis.
[0110] (Subject 5) The present invention relates to a rubber member formed of the degradable rubber composition according to any one of Subject 1 to Subject 4.
[0111] (Subject 6) The subject matter resides in that a sealing member includes the rubber member according to Subject 5 as at least a part thereof.
[0112] According to the fifth and sixth aspects, a rubber member and a sealing member can be provided which have the sealing performance of a rubber member as a sealing member and can be easily removed by being cut into small pieces even without external stress after being continuously exposed to a fluid such as water for a predetermined time.
[0113] (Subject 7) The present invention relates to a method of kneading raw materials, wherein the raw materials contain: a degradable rubber component comprising rubber molecules capable of hydrolyzing; a hydrolysis accelerator which promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an acidic hydrolysis accelerator in the form of a powder which exhibits acidity by contact with water, wherein the acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more per 100 parts by mass of the degradable rubber component.
[0114] (Subject 8) The present invention relates to a method of kneading raw materials, wherein the raw materials contain: a degradable rubber component comprising rubber molecules capable of hydrolyzing; a hydrolysis accelerator which promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor which inhibits hydrolysis of the rubber molecules; the hydrolysis accelerator comprising an alkaline hydrolysis accelerator in the form of a powder which exhibits alkalinity by contact with water, wherein the alkaline hydrolysis accelerator is contained in an amount of 1 part by mass or more per 100 parts by mass of the degradable rubber component.
[0115] According to the seventh and eighth aspects, it is possible to provide a method for producing a degradable rubber composition, which can control the time from immersion in a fluid such as water to decomposition.
[0116] [Explanation of Reference Numerals]
[0117] 1,100 Sealing components
[0118] 2 Main body
[0119] 3 Rubber components
[0120] 4 Sleeve
[0121] 5 Catheter
[0122] 10 pits
[0123] 11 Surface
[0124] 13 Digging Holes
[0125] 15 Crack
[0126] 30 Rubber Samples
[0127] 32 Small pieces of rubber sample
[0128] 34 Glass Bottle
[0129] 36 Ion exchange water
[0130] 50 Basement
[0131] 51 Mining Layer
[0132] L Length direction.
Claims
1. A degradable rubber composition, characterized in that: contain: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator that promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor, which inhibits hydrolysis of the rubber molecules, The hydrolysis accelerator includes an acidic hydrolysis accelerator, and the acidic hydrolysis accelerator is a powder that exhibits acidity when in contact with water. The acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more based on 100 parts by mass of the degradable rubber component.
2. A degradable rubber composition, characterized in that: contain: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator that promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor, which inhibits hydrolysis of the rubber molecules, The hydrolysis accelerator includes an alkaline hydrolysis accelerator, and the alkaline hydrolysis accelerator is a powder that exhibits alkalinity by contact with water. The alkaline hydrolysis accelerator is contained in an amount of 1 part by mass or more based on 100 parts by mass of the degradable rubber component.
3. The degradable rubber composition according to claim 1 or 2, wherein: The degradable rubber component includes a kneadable rubber material.
4. The degradable rubber composition according to claim 1, wherein The mass average molecular weight of the rubber molecules is greater than 10,000.
5. A rubber component, characterized in that: The degradable rubber composition according to claim 1.
6. A sealing member, characterized in that: The rubber member according to claim 5 is provided as at least a part thereof.
7. A method for producing a degradable rubber composition, characterized in that: The method comprises a mixing step of mixing raw materials, wherein the raw materials include: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator that promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor, which inhibits hydrolysis of the rubber molecules, The hydrolysis accelerator includes an acidic hydrolysis accelerator, and the acidic hydrolysis accelerator is a powder that exhibits acidity when in contact with water. The acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more based on 100 parts by mass of the degradable rubber component.
8. A method for producing a degradable rubber composition, characterized in that: The method comprises a mixing step of mixing raw materials, wherein the raw materials include: a degradable rubber component comprising rubber molecules capable of hydrolysis; a hydrolysis accelerator that promotes hydrolysis of the rubber molecules by contact with water; and a hydrolysis inhibitor, which inhibits hydrolysis of the rubber molecules, The hydrolysis accelerator includes an alkaline hydrolysis accelerator, and the alkaline hydrolysis accelerator is a powder that exhibits alkalinity by contact with water. The alkaline hydrolysis accelerator is contained in an amount of 1 part by mass or more based on 100 parts by mass of the degradable rubber component.
Citation Information
Patent Citations
Method for collection of gaseous hydrocarbon and / or liquid hydrocarbon from underground
JP2015059376A